Nutritional value of mangrove snails Littoraria melanostoma from Desa Bakau West Kalimantan - Sofiana, Mega Sari Juane; Safitri, Ikha; Nurdiansyah, Syarif Irwan; Oktavia, Oktavia (Arwana: Jurnal Ilmiah Program Studi Perairan, 2024)
Desa Bakau Village is a coastal area in Sambas Regency, West Kalimantan, which has the potential for mangrove forests with a high level of diversity. The mangrove ecosystem is a habitat for various types of biota, such as gastropods, generally known as snails. People often consume multiple gastropods using different processing methods. The nutritional content of the gastropods consumed by the people of Desa Bakau is not yet known. Therefore, this study aims to determine the nutritional composition of a gastropod from Desa Bakau (Littoraria melanostoma), including carbohydrates, protein, fat, ash content, water content, and minerals. Sampling was carried out in August 2022 in the mangrove area of Desa Bakau using the exploration method. Determination of nutritional content is carried out by referring to AOAC (2005). Proteins were analyzed by the Kjeldahl method. Fat was analyzed using the Soxhlet method. Macrominerals (Na, K, Mg, Ca, and P) were determined using an Atomic Absorption Spectrophotometer (AAS). The nutritional content of Littoraria melanostoma is water content (1.51%), ash content (22.81%), protein (49,00 %), fat (3.60%), and carbohydrates (23.08%). The highest macromineral in Littoraria melanostoma is calcium at 71.38%. Thus, this mangrove snail can be used as a good alternative source of animal protein for human consumption at a relatively affordable price.